2008
DOI: 10.1061/(asce)1084-0699(2008)13:12(1133)
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Bank Instability by Seepage Erosion Undercutting of Layered Streambanks

Abstract: Undercutting, primarily considered due to fluvial mechanisms, has been reported to have a major impact on slope failure. Predicting bank collapse specifically due to seepage erosion undercutting by particle mobilization on layered streambanks has not been fully studied or modeled, even though its role in streambank erosion may be important. The limitation originates from the limited field measurements or laboratory experiments as well as the unavailability of discrete element models that can effectively simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 29 publications
1
38
0
1
Order By: Relevance
“…Development and size of the undercut depended on the bulk density of the soil, which influenced hydraulic conductivity, cohesion, internal angle of friction, and critical hydraulic gradients to induce seepage particle mobilization. Chu-Agor et al (2008b) demonstrated that a stable bank could quickly become unstable due to seepage erosion undercutting, leading to bank failure.…”
Section: Introductionmentioning
confidence: 99%
“…Development and size of the undercut depended on the bulk density of the soil, which influenced hydraulic conductivity, cohesion, internal angle of friction, and critical hydraulic gradients to induce seepage particle mobilization. Chu-Agor et al (2008b) demonstrated that a stable bank could quickly become unstable due to seepage erosion undercutting, leading to bank failure.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical model described in this paper can explain this effect effectively. For the unstable soil, d θk is much larger than d 15 , which leads to a smaller Π. Therefore, the calculated critical hydraulic gradient was significantly smaller than that of the stable soil.…”
Section: Effect Of the Soil Internal Instabilitymentioning
confidence: 91%
“…The finer particles can be removed by the flow easily. As suggested by Kezdi [33], d 15 is assumed to be the largest movable particle in Equation (8), and, thus, D = d 15 . Figure 4 shows the distribution of the critical hydraulic gradients that were predicted under different relative exposure degrees (∆ = 0.05, 0.1, 0.2) and different porosities (e = 0.43, 0.67, 1).…”
Section: Qualitative Analysismentioning
confidence: 99%
See 2 more Smart Citations